Formation narratives: trainers’ vision about teaching practices in the pedagogy course (Revista Internacional de Formação de Professores, 2022)
The article brings to scene the narratives of teachers’ trainers who act in the context of a Pedagogy course in a federal public institution, with the objective of analyzing the senses of teachers’ trainer in the vision of those who work with teachers’ practice and supervised internship. Methodologically, it is oriented by narrative research by means of interviews with five teachers. Theoretically it is sustained in the ideas of André et. al. (2010), Marcelo Garcia (2017), Rodrigues (2009) e Roldão (2007; 2014). It was verified that the formative responsibility, the professional formation and the context of discipline mark the narratives.
Keywords: Teachers’ Trainers; Pedagogy Course; Teaching Practice; Supervised Internship; Narrative Research